Participation in school sports among children and adolescents with juvenile idiopathic arthritis in the German National Paediatric Rheumatologic Database, 2000-2015: results from a prospective observational cohort study - Florian Milatz; Jens Klotsche; Martina Niewerth; Nils Geisemeyer; Ralf Trauzeddel; Elisabeth Weißbarth-Riedel; Tilmann Kallinich; Joachim Peitz; Matthias Hartmann; Kirsten Minden (BMC, 2019)
Abstract Background Regular school sports can help adolescents achieve the recommended amount of daily physical activity and provide knowledge, attitudes and behavioral skills that are needed in order to adopt and maintain a physically active lifestyle. Furthermore, it reaches all children including those that are at risk for engaging in more sedentary types of behavior. Since adolescents with juvenile idiopathic arthritis (JIA) are less involved in physical and social activities than their healthy peers, the objectives were to (1) estimate the prevalence of participation in school sports among patients with JIA; (2) determine the correlates associated with school sports absenteeism; and (3) investigate whether attendance in school sports has changed in the era of biologics. Methods Data from schoolchildren with JIA recorded in the German National Paediatric Rheumatologic Database (NPRD) in the years 2000 to 2015 were considered for the analyses. Data from the year 2015 were inspected to analyze correlates of school sports absenteeism. Whether school sports participation had changed between 2000 and 2015 was determined using linear mixed models. Results During the 15-year period, the participation rates in school sports were determined in 23,016 patients. The proportion of patients who participated in school sports almost always steadily increased from 31% in 2000 to 64% in 2015 (β = 0.017, 95% confidence interval (CI) 0.015, 0.020), whereas the exemption rate simultaneously decreased from 44% in 2000 to 16% in 2015 [β = − 0.009, 95% CI -0.011, − 0.007]. In 2015, the data from 5879 patients (mean age 13.1 ± 3.3 years, female 65%, disease duration 5.9 ± 4.0 years, persistent oligoarthritis 37%) were available for evaluation. Full exemption from school sports (in 16.1% of cases) was associated with functional limitations, disease activity and any use of DMARDs, intra-articular glucocorticoid injections or physiotherapy. Conclusions School sports attendance among children and adolescents with JIA has increased significantly over the past 15 years. Possible explanations include improved functional ability probably due to better treatment options. The integration of patients with child acceptable symptom states who have previously been fully exempted from school sports needs to be addressed in the future.